Edutainment concept: Designing the art of kirigami sculpture for paper early childhood / Siti Ermi Syahira Abdul Jamil - Abdul Jamil, Siti Ermi Syahira (2022)
Art is a natural process in children. Beginning from infancy, children start to explore and experiment with various types of tools and art mediums. They begin to create surface marks and as they grow, the content begins to visualise. Art had become the children’s communicative way to express their understanding of the world. The children’s life skills are also able to enhance through the experiential learning process via art experience. Similarly, the edutainment concept offers a diversity form of exciting learning experiences. The concept is parallel with the young children’s biology growth as they love to play, explore, and experiment. Nowadays, there are numerous types of edutainment instruments. However, most of the instrument has only focused on digital-based commercial products. There are limited manual-based and artwork-based instruments offered by the concept. Concerning to the circumstances, the research aim is to design hybrid art instrument exclusively for the children in the early childhood stages.